STRATEGI MEMBANGUN SCHOOL BRANDING DALAM MENINGKATKAN DAYA SAING SEKOLAH DI SMK DR. SOETOMO SURABAYA - jurnalpps pps; Mustika Mustika (Prodi Magister Manajemen Universitas Wijaya Putra, 2020)
The purpose of this study was to analyze the strategic steps in building school branding. In addition, to see and analyze the supporting and inhibiting factors and their impact on increasing school competitiveness. The research method uses a qualitative approach, with data interviews and documentation studies. The results showed the strategic steps taken by schools in building school branding in increasing competitiveness, including: a) accreditation of expertise programs, b) ISO 9001: 2008, c) positive student behavior, d) student achievement both academically and non-academics, e) quality of graduates, f) superior expertise program. Supporting factors in building school branding in increasing competitiveness include a) the quality of teachers, b) the length of teaching teachers, c) teaching according to competence, d) good school promotion. While the inhibiting factors in building school branding in increasing competitiveness, include: a) motivation of students to increase competence according to expertise program, b) appearance of school buildings, c) lack of cleanliness, and d) location of the school in the middle of the campong. Keywords: strategy, school branding, competitiveness